Construction of transglutaminase covalently cross‐linked hydrogel and high internal phase emulsion gel from pea protein modified by high‐intensity ultrasound. (16th December 2022) - Wang, Yihui; Liu, Qing; Yang, Yueyue; Zhang, Ruixin; Jiao, Aiquan; Jin, Zhengyu
Abstract: BACKGROUND: The poor gelling and emulsification properties of pea protein (PeaP) limit its application in gel‐based products. In this study, a strong hydrogel and a high internal phase emulsion (HPLE) gel of PeaP were constructed by covalent cross‐linking of transglutaminase (TGase) assisted by high‐intensity ultrasound. RESULTS: Ultrasound promoted the catalytic efficiency of TGase, with the gel‐point temperature dropping from 44 °C to 28 °C after 10 min of ultrasound. As the ultrasound time increased from 1 min to 10 min, the microstructure of the hydrogel also changed from an irregular macropore structure to a relatively homogeneous honeycomb structure. This was accompanied by an improvement in gel strength, water holding capacity, and ultimate stress. Ultrasound enhanced the binding of water to PeaP, but had little effect on the water‐locking ability of the network structure. Ultrasonication improved the self‐supporting ability of the HPIE gels. The oil droplets within the HPIE gels were closely aligned to form a hexagonal structure. The PeaP layer was further cross‐linked by TGase, strengthening the network structure. High internal phase emulsion gel displayed a higher gel strength, viscosity, and good self‐healing ability under 1 min ultrasound. Meanwhile, HPIE gel at 1 min of ultrasound could be printed with the highest clarity. CONCLUSION: This work provided some insights into improving the functional properties of PeaP, which is helpful for the design and development of PeaP‐based gel products. © 2022 Society of Chemical Industry.